Desarrollo de un modelo matemático para cuantificar la evaporación de las fases líquidas de los fluidos de perforación base aceite en las operaciones de Piedemonte (2017)
In the present thesis work, a mathematical model is developed to quantify the losses due to evaporation of the liquid phases of the oil based drilling fluids used in the Piedemonte block field operations. For the development of the model, laboratory tests were performed, identifying three main variables that affect the evaporation of inverse emulsion type fluids, which are: contact area, temperature at the exit of the flow line and relation water-oil emulsion.